Internalisasi Nilai-Nilai Moderasi Beragama pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Dasar - Mutohir, Arif (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2025)
This research aims to explore two main aspects: first, the internalization of religious moderation values and the existence of Islamic Religious Education subjects at Kebonagung State Elementary School; second, the factors that support and hinder the internalization process. Using a descriptive and phenomenological qualitative approach, this research collected data from two main sources: primary and secondary data. Primary and secondary data. Data collection techniques include observation, interviews, and documentation studies. The results showed some interesting findings: first, the internalization of religious moderation values in Kebonagung State Elementary School, Babat Subdistrict, Lamongan Regency can form tolerant attitudes and personalities, encourage students' scientific spirit and creativity, and build fair and balanced characters among students. Second, the existence of Islamic Religious Education is very crucial in improving the quality of learning at improving the quality of learning at Kebonagung State Elementary School, Babat Subdistrict, Lamongan Regency. In addition, the factors that support and hinder the internalization of religious moderation values are interrelated, with the aim of developing students' potential according to their respective talents and interests.